The crystal structure of N-(3-bromo-4-fluorophenyl)-N′-hydroxy-4-{[2-(4-methylphenyl)ethyl]amino}-1,2,5-oxadiazole-3-carboximidamide, C18H17BrFN5O2 - Zuo Limin; Zhou Xia; Liu Yitong; Gu Yongsheng; Jiang Yifei; Lian Xiaofang; Liu Huiyi; Jia Qingying; Shan Guangzhi (Zeitschrift für Kristallographie - New Crystal Structures)
C18H17BrFN5O2, monoclinic, P21/c (no. 14), a = 19.3571(8) Å, b = 13.4295(12) Å, c = 7.3036(5) Å, β = 93.372(5)°, V = 1895.3(2) Å3, Z = 4, Rgt(F) = 0.0407, wRref(F2) = 0.0939, T = 293(2) K.